PENERAPAN PROSEDUR SNI DALAM UJI BANDING LABORATORIUM Analisa Kadar Proksimat dalam Powdered Tonic Food Drink - Oman Zuas; Nuryatini Nuryatini; Dyah Styarini (JURNAL STANDARDISASI, 2009)
The primary objective of proficiency testing (PT) is in the provision of information and support to participatinglaboratories, to enable them to monitor and improve the quality of their measurements. However, other benefitscan be obtained from PT. These include the comparison of data for a given measurement by different methods,the validation of new methods, and the provision of information for laboratories' customers and accreditationbodies. This paper reports on the subject of the participation of Puslit Kimia LIPI on PT for proximate analysis(ash, moisture, and fat content) in Powdered Tonic Food Drink (PTFD) by using SNI: 01-2891-1992. This PT wasorganized by Food and Nutrition Research Institute (FNRI)-Philippines. The PT scheme comprisses of theselection of analysis method, method verification, and analysis of proximate in PTFD sample followed byestimating its uncertainty. The final evaluation of PT by FNRI reported that Puslit Kimia LIPI has achieved asatisfactory result for proximate analysis in the PTFD sample. From this standpoint, it can be concluded that theSNI: 01-2891-1992 has shown great performance and gave comparable result to other participants from othercountries involved in this PT.